The Effect of Emigration from Poland on Polish Wages - Christian Dustmann; Tommaso Frattini; Anna Rosso (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
This paper analyses the effect of emigration from Poland around the time of EU accession on the Polish labour market. We develop a simple model that guides our empirical specification and provides a clear interpretation for our estimates. Focussing on the 1998-2007 period for Poland, we use a unique data set that contains information about household members who are currently living abroad, which allows us to develop region-specific emigration rates and estimate emigration's effect on wages using within-region variation. Our results show that emigration from Poland was largest for workers with intermediate-level skills and that it is wages for this skill group that increased most. We also show that emigration led to a slight increase in wages overall but that workers at the low end of the skill distribution made no gains and may actually have experienced slight wage decreases.
Keywords: J31; J61; 330; Emigration; Wages; Impact